Changes in the latent structure of motor space of boys during puberty - Jurak, Gregor (Kinesiologia Slovenica, 2003)
We analysed the latent structure of the motor space of boys at the ages of 11,13, 15 and 17. The transversal study was carried out on a representative sample of 517 subjects within the larger research work of Strel et al. (1996). The assessment of motor abilities was made by conducting 26 tests covering all hypothetical motor dimensions. The latent structure was studied using the classic procedures of factor analysis. We found differences in the latent structure of motor space in different age periods. For younger individuals who were tested, achievements depended on the simultaneous impact of various functional mechanisms and therefore the structure of latent space is less precisely defined. Motor abilities gradually differentiate with increased age. At the age of 15 we can notice a repercussion of movement patterns. The sensitivity of that age period demands that sports teachers take a closer look at the physical and motor development of young people and to tailor exercises according to personal development.
Keywords: adolescenca; dečki; latentna struktura; motorične sposobnosti